(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The morning glory (MG) syndrome is a rare, sporadic and commonly unilateral anomaly. The MG and persistent fetal vasculature (PVF) syndromes are generally considered as isolated ocular manifestations of failures in various stages of embryogenesis of the eye. Purpose: To describe the clinical manifestations of a bilateral combined ocular pathology, the MG syndrome and PVF syndrome, associated with congenital central nervous system (CNS) and bone anomalies. Material and Methods: We described a rare variant of binocular manifestation of the MG syndrome associated both with the PVF syndrome and CNS involvement in a 7-month infant. Results: In the pediatric case reported here, the bilateral combination of MG syndrome and PVF syndrome is accompanied by congenital CNS anomalies, corpus callosum agenesis and vicarious ventriculomegaly. To the best of our knowledge, this congenital association has been not reported previously, which made us to report this case. Conclusion: Morning glory syndrome is a rare congenital disorder whose pathogenesis is still not fully understood. The rare infant case reported here demonstrates an association of the MG syndrome with another congenital anomaly of the eye (the persistent fetal vasculature syndrome) and a major congenital anomaly of the CNS, corpus callosum agenesis, which requires not only detailed and comprehensive medical evaluation, but also longitudinal patient surveillance in cooperation with allied specialties like neuropathology, pediatrics, etc.